2003
DOI: 10.1007/s00402-003-0538-4
|View full text |Cite
|
Sign up to set email alerts
|

Surgical treatment of fractures of the distal radius with plates: a comparison of palmar and dorsal plate position

Abstract: This study shows that the majority of patients with problem fractures of the distal radius can be successfully treated by internal fixation using the T-plate. The dorsal approach to the distal radius--in cases where dorsal plating is appropriate--will result in a better anatomical reduction and clinical outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
27
0
7

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 17 publications
1
27
0
7
Order By: Relevance
“…2 Thus far, few studies compared the volar and dorsal plate position in the surgical treatment of fractures of the distal radius including different kinds of distal radius fractures according to the Association for Osteosynthesis (AO) classification. 1,4,9,10 Most clinical studies only reported the outcome of either volar or dorsal plate osteosynthesis. 2,5,8 Therefore, exact comparison of the outcome of intra-articular comminuted fractures between volar and dorsal plate osteosynthesis is not possible as, for example, type A fractures are extra-articular.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…2 Thus far, few studies compared the volar and dorsal plate position in the surgical treatment of fractures of the distal radius including different kinds of distal radius fractures according to the Association for Osteosynthesis (AO) classification. 1,4,9,10 Most clinical studies only reported the outcome of either volar or dorsal plate osteosynthesis. 2,5,8 Therefore, exact comparison of the outcome of intra-articular comminuted fractures between volar and dorsal plate osteosynthesis is not possible as, for example, type A fractures are extra-articular.…”
mentioning
confidence: 99%
“…3 The dorsal approach is usually favored in patients with excessive dorsal comminution or displacement that are not amenable to indirect reduction via a volar approach. 1 The dorsal approach, however, is controversial because of extensor tendon complications. 2,4,5 Recently, the treatment of volar fixation of dorsally unstable distal radius fractures with a fixed-angle plate was introduced to avoid extensor tendon complications of dorsal plates.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1 Displaced, unstable fractures are typically treated by anatomic reduction and stable fixation using plates. 2 Since the late 1980s, dorsal plates have been effectively used to maintain radiographic alignment of dorsally displaced distal radius fractures.…”
mentioning
confidence: 99%
“…Fixed-angle volar plating has been shown clinically to hold reduction of volar tilt and radial inclination reliably until the fracture heals. 2,3,9,14,18 The fracture model that we have created also represents a second clinical situation. Distal radius fractures that have healed with malunion can be treated with an osteotomy.…”
Section: Discussionmentioning
confidence: 99%